Nutrition of the lactating beef cow - Somerville, Stuart H. (The University of Edinburgh, 1977)
The primary purpose of this thesis was to examine the evidence relating to the effect of nutrition on the performance of single - suckled beef cows and to determine experimentally the response of autumn - calving Hereford cross British Friesian cows to three levels of energy intake during lactation.

The different methods available for measuring the milk production of beef cows were discussed on the basis of information reported in the literature and two of the methods, machine -milking twice a day and a calf -suckling technique compared experimentally. It was concluded that the calf -suckling technique described is the more reliable and precise method of measuring milk production.

Two experiments were reported in each of which 36 beef cows were offered individually either 175 per cent of their estimated energy requirement for maintenance (high), 125 per cent (medium), or 90 per cent (low), during the first 150 days of lactation. The rations offered consisted of grass silage and a barley -based concentrate supplement.

The estimated 150 -day cumulative milk yields of beef cows in their second lactation, measured by a calf -suckling technique, were 1385 kg, 1274 kg and 1197 kg (P <0.01) on the high, medium and low planes of nutrition respectively. The corresponding figures for live -weight loss between parturition and 150 days post partum were 31 kg, 87 kg and 139 kg (P <0.001). The results demonstrated that energy deficient beef cows will attempt to sustain milk production by mobilising body reserves. It was also demonstrated that the growth rate of a suckled calf is sensitive to a reduction in milk intake during its first 150 days of life, but the weaning weights of autumn-born calves appeared unaffected by the plane of nutrition received by their dams during the winter.

The implications of the results and areas of future research were discussed.